Tight control of nitrate acquisition in a plant species that evolved in an extremely phosphorus‐impoverished environment. (2nd November 2016) - Prodhan, M. Asaduzzaman; Jost, Ricarda; Watanabe, Mutsumi; Hoefgen, Rainer; Lambers, Hans; Finnegan, Patrick M.
Abstract: Hakea prostrata (Proteaceae) has evolved in an extremely phosphorus (P)‐limited environment. This species exhibits an exceptionally low ribosomal RNA (rRNA) and low protein and nitrogen (N) concentration in its leaves. Little is known about the N requirement of this species and its link to P metabolism, despite this being the key to understanding how it functions with a minimal P budget. H. prostrata plants were grown with various N supplies. Metabolite and elemental analyses were performed to determine its N requirement. H. prostrata maintained its organ N content and concentration at a set point, independent of a 25‐fold difference nitrate supplies. This is in sharp contrast to plants that are typically studied, which take up and store excess nitrate. Plants grown without nitrate had lower leaf chlorophyll and carotenoid concentrations, indicating N deficiency. However, H. prostrata plants at low or high nitrate availability had the same photosynthetic pigment levels and hence were not physiologically compromised by the treatments. The tight control of nitrate acquisition in H. prostrata retains protein at a very low level, which results in a low demand for rRNA and P. We surmise that the constrained nitrate acquisition is an adaptation to severely P‐impoverished soils. Abstract : Hakea prostrata (Proteaceae), naturally occurring on extremely phosphorus‐impoverished soils, responds to nitrogen availability in a fundamentally different way from that of model plants like Arabidopsis . Instead of accumulating nitrogen, H. prostrata tightly controls its nitrogen acquisition, independent of availability, maintaining a low total and organ nitrogen concentration. This reduces its phosphorus requirement for ribosomal RNA, the major leaf organic phosphorus fraction, contributing to its survival on phosphorus‐impoverished soils. Our results on plant functioning in an extreme environment are likely valuable in developing phosphorus‐use efficient crops, and thus of interest to many plant biologists.